A processing method for orthodontic mini-screws reuse - Saeed Noorollahian; Shiva Alavi; Mohammad Monirifard (Wolters Kluwer Medknow Publications, 2012)
Background: The possibility of mini-screws reuse would reduce treatment cost. The aim of this study is to introduce a new method (application of phosphoric acid 37% for 10 minutes followed by sodium hypochlorite 5.25% for 30 minutes) for cleansing of mini-screws and assessing the efficacy of this method. The effects of this processing on the insertion, removal, and fracture torques of mini-screws were evaluated. Materials and Methods: This experimental study was done in two parts. In part I the amount of calcium ion on mini-screws surfaces as an index of tissue remnants was assessed. In part II of this study, the effects of previous use, processing method, and resterilization on the insertion, removal, and fracture torques of mini-screws were assessed. Each part of this study had 3 groups; non-processed used (NP), processed used (P), and as-received (C). Each group had 16 samples in part I and 20 samples. Non parametric statistical tests were used in part I and one way ANOVA in part II. Results: The mean amount of calcium ion in groups non-processed (NP1), processed (P1), and control (C1) were 4.7, 0.43, and 0.02 ppm, respectively. The amount of calcium ion in group NP1 was significantly greater than in the other groups (P = 0.000), but the difference between groups P1 and C1 was not significant (P = 0.087). The mean insertion torque of group NP2 was lower than that of other groups (P < 0.05) but P2 and C2 did not have significant differences (P = 0.988). The mean of removal and fracture torque did not have significant differences among all groups. Conclusion: Cleaning of used mini-screws with phosphoric acid 37% (10 minutes) and sodium hypochlorite 5.25% (30 minutes) reduces tissue remnants to the level of as-received mini-screws. So it can be suggested as a processing method of used mini-screws. Previous insertion of mini-screws into the bone and above-mentioned processing method and resterilization with autoclave had no adverse effects on insertion, removal, and fracture torque values as mechanical properties indices.